If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 + -6x = 7x + 2 Reorder the terms: 2 + -6x = 2 + 7x Add '-2' to each side of the equation. 2 + -2 + -6x = 2 + -2 + 7x Combine like terms: 2 + -2 = 0 0 + -6x = 2 + -2 + 7x -6x = 2 + -2 + 7x Combine like terms: 2 + -2 = 0 -6x = 0 + 7x -6x = 7x Solving -6x = 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. -6x + -7x = 7x + -7x Combine like terms: -6x + -7x = -13x -13x = 7x + -7x Combine like terms: 7x + -7x = 0 -13x = 0 Divide each side by '-13'. x = 0 Simplifying x = 0
| 20g^2=16g | | 8+3(4x-4)=5-4(2x+1) | | X=6+-1y+-1z | | -24c^2=36 | | 3x-y=-3 | | (x+2)(x-1)=40 | | 3m=2 | | 6d=0 | | 3x+12=7x-16 | | 3x+12=7x-17 | | 4x-6x+3=2x+11 | | 5x+4=3x-2x+4x | | y=2.2 | | 13+5=6E+(-4)+(-5) | | -3u^2+19u-24=0 | | 4x^2-32x-17=0 | | x^4+4x^2=77 | | 5x^2+17x+14=0 | | 2x^2+15xy+7y^2=0 | | 5=ln(x+1) | | 0.0308.12= | | 26x^2-160x+211=0 | | 14x^2+15x+4=0 | | 6t+2(1-4t)= | | n+6=9 | | -5+6=x | | 2(4p-3)=4+2p | | 7x+-49+18= | | 13x-5(x-2)=8x+5 | | m-9=-3 | | 7x+7-6x=9 | | 6x^2=1296 |